Hydrolysis and drug release from poly(ethylene glycol)-modified lactone polymers with open porosity. (April 2019) - Asikainen, Sanja; Paakinaho, Kaarlo; Kyhkynen, Anna-Kaisa; Hannula, Markus; Malin, Minna; Ahola, Niina; Kellomäki, Minna; Seppälä, Jukka
Graphical abstract: Highlights: Drug-releasing structures have potential as bone regeneration inducing scaffolds. The active agents did not affect the formation of pore architecture prepared by scCO2 . The polymer properties affected drug release more than the pore architecture. Abstract: The ability to release active agents from a porous scaffold structure in situ enables the simultaneous structural support for the cells proliferating and differentiating towards tissue as well as the stimulation of tissue regeneration. Due to the great potentiality of such approach, drug-releasing scaffolds were fabricated from hydrolytically degradable polymers. Three copolymers of poly(ethylene glycol), ɛ-caprolactone, l - and d, l -lactide were synthesized and blended with bone-growth inducing active agents, dexamethasone (DM) and 2-phospho-l -ascorbic acid trisodium salt (AS). Porous scaffolds were prepared by means of super-critical carbon dioxide foaming. In the final scaffold structures, the particle size, location and the water solubility of the drug affected the release kinetics. As the large and water soluble AS particles were more exposed to the buffer solution compared to small DM particles, the AS release was burst-like whereas DM showed a long-term release. The material structure had a significant effect on the release kinetics as the porous scaffolds released active agents faster compared to the solid cylinders. Furthermore, this study showed the strong effect of polymer degradation and wettability on the release, which were more determinative than the pore architecture.